2018
DOI: 10.1111/1751-7915.13332
|View full text |Cite
|
Sign up to set email alerts
|

Improved protein production and codon optimization analyses in Escherichia coli by bicistronic design

Abstract: SummaryDifferent codon optimization algorithms are available that aim at improving protein production by optimizing translation elongation. In these algorithms, it is generally not considered how the altered protein coding sequence will affect the secondary structure of the corresponding RNA transcript, particularly not the effect on the 5′‐UTR structure and related ribosome binding site availability. This is a serious drawback, because the influence of codon usage on mRNA secondary structures, especially near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…, 2013; Nieuwkoop et al . , 2019). Comparison of the measured translation efficiency of mRNAs in our data set with that predicted by RBS Calculator (Salis et al , 2009; Salis, 2011) (Table S1, Predicted translation efficiency) demonstrated relatively good, although not ideal correlation ( r = 0.62).…”
Section: Resultsmentioning
confidence: 99%
“…, 2013; Nieuwkoop et al . , 2019). Comparison of the measured translation efficiency of mRNAs in our data set with that predicted by RBS Calculator (Salis et al , 2009; Salis, 2011) (Table S1, Predicted translation efficiency) demonstrated relatively good, although not ideal correlation ( r = 0.62).…”
Section: Resultsmentioning
confidence: 99%
“…They found that weakly structured ribosome binding sites result in high red fluorescent protein levels. This was supported by recent studies using the endogenous folA and adk genes 48 and a dual-reporter system in E. coli 49 . These studies, and many others, support our finding that optimisation of the accessibility of translation initiation sites is a key to improve heterologous protein production.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have used minimum free energy models to define the accessibility of a region of interest 27,48,49 . However, we have discovered that the opening energy is a better choice for modelling accessibility (see Fig 1A for example).…”
Section: Discussionmentioning
confidence: 99%
“…With using a well-expressed N-terminal protein fusion such as GST, G-CSF isoform D was successfully expressed. 22 We used GST as a fusion expression partner for two main reasons: First, GST as one of the most common fusion tags greatly enhances the expression of difficult-toexpress recombinant proteins by allowing the efficient initiation of translation. 23 High levels expression of the GST-fusion proteins in E. coli may result in the formation of inclusion bodies, as we observed in our experiment.…”
Section: Discussionmentioning
confidence: 99%